Ketimpangan Pembagian Warisan bagi Perempuan dalam Perspektif KHI: Studi Kasus di Langkat Sumatra Utara - Joni Benre; Irwansyah (Universitas Islam Tribakti Lirboyo Kediri, 2025)
This study aims to analyze the inheritance distribution process in Paya Village, which often becomes a source of conflict in many families. The main focus of this research is to understand the practice of inheritance distribution that does not comply with the applicable legal provisions, particularly in the context of the Compilation of Islamic Law (KHI). The research employs an empirical normative method, where data were collected through interviews and field observations, as well as a review of relevant legal regulations, including the KHI and the Qur'an, specifically Surah An-Nisa verse 11. The findings reveal that inheritance distribution in Paya Village frequently deviates from the provisions stipulated in the KHI. The practices show a tendency for the eldest child to receive a larger share, thereby reducing the rights of female heirs. This injustice in distribution often triggers sensitive social issues, including disputes and conflicts among family members over inheritance rights. The study emphasizes that the inheritance practices that do not align with the KHI, particularly Article 176, have the potential to cause societal conflicts. Therefore, it is essential to enhance public understanding of inheritance law to ensure that inheritance distribution is conducted fairly and in accordance with Islamic principles.